2022
DOI: 10.3389/fcimb.2022.805481
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Short-Chain Fatty Acid Modulation on Potentially Diarrhea-Causing Pathogens in Yaks Through Metagenomic Sequencing

Abstract: Short-chain fatty acids (SCFA) are principal nutrient substrates of intestinal epithelial cells that regulate the epithelial barrier in yaks. Until now, metagenomics sequencing has not been reported in diarrheal yaks. Scarce information is available regarding the levels of fecal SCFA and diarrhea in yaks. So, our study aims to identify the potential pathogens that cause the emerging diarrhea and explore the potential relationship of short-chain fatty acids in this issue. We estimated diarrhea rate in yaks afte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 97 publications
(113 reference statements)
2
12
0
Order By: Relevance
“…In our previous study, we found a significant decrease in concentrations of SCFAs, especially acetic acid and butyric acid in yaks ( Li et al, 2022 ). We hypothesized that sodium acetate/sodium butyrate supplementation could alleviate diarrhea in animals, similar to how Lactobacillus plantarum alleviated diarrhea in a previous study by balancing gut microbiota and regulating SCFAs ( Yue et al, 2020 ).…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…In our previous study, we found a significant decrease in concentrations of SCFAs, especially acetic acid and butyric acid in yaks ( Li et al, 2022 ). We hypothesized that sodium acetate/sodium butyrate supplementation could alleviate diarrhea in animals, similar to how Lactobacillus plantarum alleviated diarrhea in a previous study by balancing gut microbiota and regulating SCFAs ( Yue et al, 2020 ).…”
Section: Introductionmentioning
confidence: 78%
“…Diarrhea is a severe disease coupled with gastrointestinal dysfunction that has a global impact on fertility rate, milk production, and immunity in livestock ( Coura et al, 2015 ; Li et al, 2022 ). Nowadays diarrhea in dairy cows and yak is very serious.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Butyrate constitutes a key source of energy for enterocytes and has a trophic effect on the colon epithelium, supporting the restoration of the disrupted structural and functional integrity of the epithelial barrier [ 17 ]. Butyrate may also affect the composition of intestinal microbiota by inhibiting the proliferation of pathogens and fostering desirable strains [ 18 ]. Moreover, butyrate beneficially affects several inflammatory cytokines and myeloperoxidase activity via inhibition of nuclear factor kappa B [ 19 ].…”
Section: Introductionmentioning
confidence: 99%